2016
DOI: 10.1080/10942912.2016.1212874
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial drug residues in poultry products and implications on public health: A review

Abstract: Poultry meat and eggs are important foods for fulfilling the dietary needs of the ever-growing human population. Efficient poultry production, however, necessitates use of pharmaceutical products, such as antibiotics, as prophylactic and curatives to ensure rapid growth and health. Nevertheless, inappropriate and non-judicious use of these drugs results in an accumulation of toxic and harmful residues in meat and eggs of treated birds which affect consumer health by triggering allergic reactions and transmitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
93
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(107 citation statements)
references
References 69 publications
(80 reference statements)
6
93
0
8
Order By: Relevance
“…The improper administration or misuse of tilmicosin can result in elevated residual levels in animal source foods. Previous studies have reported that there exist various forms of health risks associated with the drug residue contamination of food, including skin allergies, gastrointestinal system reactions, anaphylactic shock, liver damage, and thrombophlebitis (Heshmati, Kamkar, Salaramoli, Hassan, & Jahed, ; Mund, Khan, Tahir, Mustafa, & Fayyaz, ; Nisha, ). However, the most common healthy risk is that of allergic reactions (Bigby, Jick, & Arndt, ; Oslon & Sanders, ).…”
Section: Introductionmentioning
confidence: 99%
“…The improper administration or misuse of tilmicosin can result in elevated residual levels in animal source foods. Previous studies have reported that there exist various forms of health risks associated with the drug residue contamination of food, including skin allergies, gastrointestinal system reactions, anaphylactic shock, liver damage, and thrombophlebitis (Heshmati, Kamkar, Salaramoli, Hassan, & Jahed, ; Mund, Khan, Tahir, Mustafa, & Fayyaz, ; Nisha, ). However, the most common healthy risk is that of allergic reactions (Bigby, Jick, & Arndt, ; Oslon & Sanders, ).…”
Section: Introductionmentioning
confidence: 99%
“…The transition of antibiotics into food products is associated with their widespread use in animal husbandry for therapeutic and prophylactic purposes, as well as with their application as growth-stimulating agents for farm animals and poultry. 3 In addition, there is the problem of the illegal use of antibiotics, in particular, to extend the shelf life of foodstuffs. 4 Such practices can lead to the transmission of antimicrobials along the food chain and the accumulation of residual amounts of antibiotics in the food products of end users.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the world, there is an emerging public health crisis and a growing concern regarding the potential for the development of antimicrobial resistance (AMR) that can occur as a result of the selective pressure and dissemination of resistance caused by unscrupulous misuse and inappropriate antimicrobial usage [1,9,13,19]. Over time, 10 the restriction of antibiotic usage has been encouraged, if not enacted through legislation, in an attempt to prevent such AMR development due to non-rational veterinary antimicrobial use [10].…”
Section: Introductionmentioning
confidence: 99%
“…Such presence of antimicrobial residues can result in direct toxicity or indirectly in AMR. Antimicrobial residue levels in the edible tissues of livestock, including poultry, should be monitored via detection methods (screening and subsequent confirmation) and assessed regularly to ensure that the food of animal origin is safe and wholesome for consumers and does not contain antimicrobial residues at levels which exceed the established Maximum Residue Limits (MRLs) as defined by legislation [4,13].…”
Section: Introductionmentioning
confidence: 99%